The Role of IL-6 in Cancer Cell Invasiveness and Metastasis-Overview and Therapeutic Opportunities - Rašková, Magdalena; Lacina, Lukáš; Kejík, Zdeněk; Venhauerová, Anna; Skaličková, Markéta; Kolář, Michal; Jakubek, Milan; Rosel, Daniel; Smetana, Karel; Brábek, Jan (Cells, 2022)
Interleukin 6 (IL-6) belongs to a broad class of cytokines involved in the regulation of various homeostatic and pathological processes. These activities range from regulating embryonic development, wound healing and ageing, inflammation, and immunity, including COVID-19. In this review, we summarise the role of IL-6 signalling pathways in cancer biology, with particular emphasis on cancer cell invasiveness and metastasis formation. Targeting principal components of IL-6 signalling (e.g., IL-6Rs, gp130, STAT3, NF-κB) is an intensively studied approach in preclinical cancer research. It is of significant translational potential; numerous studies strongly imply the remarkable potential of IL-6 signalling inhibitors, especially in metastasis suppression.
Keywords: Antineoplastic Agents; metastasis; signální transdukce; Interleukin-6; nádory; lidé; protinádorové látky; Neoplasms; IL-6; interleukin-6; cancer; Humans; Signal Transduction